Factors affecting marital satisfaction and marital communication among marital women: literature of review - Khezri, Zahra; Hassan, Siti Aishah; Mohamed Nordin, Mohd Hamdan (Human Resource Management Academic Research Society, 2020)
This paper provides a comprehensive methodological review of the literature assessing the factors affecting marital satisfaction and marital communication among marital women. This systematic review surveys published articles from 1981 to 2017. First, scientific databases such as Pubmed/Medline, Scopus, Elsevier, and Cochran library, Springer, Scientific Information Database (SID), IranMedex, Magiran and Medlib were searched using relevant key words and phrases. All published peer reviewed articles studied exploring associations between marital satisfaction and effective factors were considered for inclusion. The findings indicated that the income and eco-nomic status can exert a positive effect on the couple’s satisfaction which can be one of the important factors affecting marital satisfaction. According to the results of these articles, the influential effect of some factors such as occupation, length of marriage, age, Number of children, economic factor and income had been emphasized. In mate selection, it is necessary to note various criteria, including religious matters, moral, mental health, communication skills and sexual factor and action through education, counseling and treatment if there is problem.